Investigating the Relationship between Organizational Commitment and Climate with Public Health (Case Study: Physical Education Teachers in Kermanshah Province) - Mohammad Saeid Kiani; Leila Nazari (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: Appropriate organizational climate can be effective in motivating and improving the morale and participation of people in their decisions and creativity and innovation and can be considered as a source in ensuring the mental health of employees. However, inappropriate atmosphere can also be a major source of stress. The purpose of this study was to investigate the relationship between organizational commitment and organizational climate with the general health of physical education teachers in Kermanshah province.Methodology: The statistical population of the present study was 1200 physical education teachers in Kermanshah province, and according to the Morgan table, 291 people were selected as a sample through systematic random sampling. Four questionnaires of demographic characteristics were used to measure the variables: the Mir and Allen questionnaire (1996), the questionnaire (OCDQ-RS), and the Goldberg and Hiller questionnaire (2012). Formal and content validity was confirmed by opinion polls from related professors, and the reliability of the questionnaires was reported to be 0.79, 0.87, and 0.79 using Cronbach's alpha. Descriptive statistics were used to describe the variables, and inferential statistics were used to test the research hypotheses at a significance level of α ≤ 0 0.05.Findings: The results indicated a significant difference between the dimensions of organizational commitment (P = 0.008), organizational climate (P = 0.001), and general health (P = 0.001) of teachers. There was a significant difference between organizational commitment and different levels of public health (P = 0.024). Still, no significant difference was observed between organizational climate and different levels of public health (P = 0.152).Originality/Value: Notably, the physical education sector of the education category needs specialized and capable people to put their knowledge to the application stage, no matter the organizational climate and commitment. If physical education teachers are in better condition, they will have more general health and can be more motivated to move towards the goals of the organization.